2020
DOI: 10.1371/journal.pone.0242423
|View full text |Cite
|
Sign up to set email alerts
|

First trimester secreted Frizzled-Related Protein 4 and other adipokine serum concentrations in women developing gestational diabetes mellitus

Abstract: Background The aim of this study was to evaluate whether soluble frizzled-related protein 4 (sFRP4) concentration in the first trimester of pregnancy is individually, or in combination with Leptin, Chemerin and/or Adiponectin, associated with the development of gestational diabetes (GDM). Methods In a nested case-control study, 50 women with GDM who spontaneously conceived and delivered a live-born infant were matched with a total of 100 uncomplicated singleton control pregnancies based on body mass index (±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 67 publications
2
11
1
Order By: Relevance
“…Of the 9 cord blood proteins associated with birth weight and body anthropometrics in this study, 3 are associated with metabolism or metabolic disorders. High serum whole blood afamin and SFRP4 concentrations in the first trimester have been associated with the onset of gestational diabetes . Both afamin overexpression in transgenic mice and gestational diabetes in humans have been associated with a higher birth weight and/or increased risk of large for gestational age, which is in line with the findings of this study.…”
Section: Discussionsupporting
confidence: 90%
“…Of the 9 cord blood proteins associated with birth weight and body anthropometrics in this study, 3 are associated with metabolism or metabolic disorders. High serum whole blood afamin and SFRP4 concentrations in the first trimester have been associated with the onset of gestational diabetes . Both afamin overexpression in transgenic mice and gestational diabetes in humans have been associated with a higher birth weight and/or increased risk of large for gestational age, which is in line with the findings of this study.…”
Section: Discussionsupporting
confidence: 90%
“…PCSK9 [79], APCDD1 [80], SFRP4 [81], MFAP5 [82] and PKP2 [83] are associated to the risk of obesity. Studies show that PCSK9 [84] and SFRP4 [85] are involved in the process of gestational diabetes mellitus. The PCSK9 [86], SEMA3A [87], SFRP4 [81] and BMP6 [88] were found as potential biomarkers for diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Secreted frizzled-related protein 4 (sFRP4) has been shown to play a role in glucose metabolism, reflecting islet inflammation and impaired insulin secretion [ 325 ]. Schuitemaker et al [ 326 ] found significantly higher first-trimester levels of sFRP4 in women, who subsequently developed GDM (n = 50, diagnostic criteria fasting glucose ≥ 7.0 mmol/L, 2 h glucose ≥ 7.8 mmol/L) compared to controls and a predictive capacity expressed as AUC of 0.60 (95% CI 0.50–0.70). The correlation between sFRP4 and GDM is supported by other studies [ 327 , 328 ]…”
Section: Discussionmentioning
confidence: 99%